Impact of Arbuscular Mycorrhizal Fungi, Phosphate Solubilizing Bacteria and Selected Chemical Phosphorus Fertilizers on Growth and Productivity of Rice - Nehal M. Elekhtyar; Mamdouh M. A. Awad-Allah; Khalid S. Alshallash; Aishah Alatawi; Rana M. Alshegaihi; Reem A. Alsalmi (Agriculture, 2022)
Phosphorus is the second most significant macro nutrient in rice productivity. Phosphorus fixation in Egyptian soil makes it unavailable for rice to absorb. The goal of this study was to examine the effects of microbial and chemical sources of phosphorus fertilizers on the Egyptian Sakha 106 rice cultivar by applying different sources of phosphorus to increase the bioavailability of soil phosphorus for plants and to allow it to be fixed biologically to change it from an insoluble form to a soluble and available form for rice to absorb. So, in the 2019 and 2020 seasons, a field experiment was conducted at the experimental farm of Sakha Agricultural Research Station, Sakha, Kafr El-Sheikh, Egypt. The experiment was carried out using a Randomized Complete Block Design with four replications to determine the best phosphorus source for rice and soil among various treatments, which included 100% single super phosphate (SSP) basal application (P1), 75% single super phosphate (SSP) basal application (P2), P2 + phosphate-solubilizing bacteria (PSBs) top-dressing, P2 + arbuscular mycorrhizal fungi (AMFs) top-dressing P2 + phosphorus nanoparticles (PNPs) foliar spraying, P2 + phosphoric acid (PA) foliar spraying, P2 + (PSBs + AMFs) foliar spraying, P2 + (PSBs + PNPs) foliar spraying, P2 + (PSBs + PA) foliar spraying, P2 + (PNPs + PA) foliar spraying, P2 + (PSBs + PNPs + PA) foliar spraying and zero-phosphorus fertilizer. The results showed that the highest values were mostly obtained using the combination of 75% SSP basal application with the foliar spraying of PSBs, PNPs and PA, with substantial beneficial impacts on the leaf area index (3.706 and 3.527), dry matter accumulation (464.3 and 462.8 g m2), plant height (96.33 and 95.00 cm), phosphorus uptake in grain (24.3 and 24.49 Kg ha−1), phosphorus uptake in straw (17.7 and 17.0 Kg ha−1) and available phosphorus in the soil at harvest (21.75 and 21.70 ppm) in the 2019 and 2020 seasons, respectively; moreover, 75% SSP basal application with the foliar spraying of PSBs, PNPs and PA or 100% SSP basal application alone improved the number of panicles (506.3 or 521.1 and 521.9 or 547.1 m−2), filled grain weight (3.549 or 3.534 and 3.627 or 3.767 g panicle−1), the percentage of filled grain (96.19 or 96.47 and 95.43 or 96.24%), grain yield (9.353 or 9.221 and 9.311 or 9.148 t ha−1) and straw yield (11.51 or 11.46 and 11.82 or 11.69 t ha−1) in the 2019 and 2020 seasons, respectively. Chemical P fertilizers combined with the foliar spraying of PSBs, PNPs and PA obtained the highest crop productivity and improved most of the examined characteristics without any significant changes with respect to chemical P application alone in some other characteristics, followed by 75% SSP + top-dressing with PSBs + AMFs. The treatment that included the combination of 75% SSP basal application and the foliar spraying of PSBs +PNPs +PA is recommended, as it might be utilized to boost rice yield by solubilizing P in soil and increasing the absorption efficiency. In addition, it reduces chemical P fertilizers by 25%, which would guarantee a cleaner environment and soil conservation.